1989
DOI: 10.1002/kin.550210809
|View full text |Cite
|
Sign up to set email alerts
|

Unusual selectivities of radical reactions. Experimental studies on alkyl versus phenoxyl reaction systems

Abstract: Radical reactions involving two or more intermediates and many mutual reaction channels may lead to the specific formation of one cross-reaction product if one species is rather persistent and if transient and persistent species are produced with equal rates. A previous kinetic analysis of the phenomenon revealed that the concentrations of the intermediates and the selectivities of product formation depend critically on the relative initiation rates. The present experimental ESR studies on systems involving si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…Note that the steady state kinetics of the system just described has been studied theoretically by Hanns Fischer, 9 and the predictions of the theory were later tested by experiment. 28 The present study, on the other hand, addresses the question of transient kinetics.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Note that the steady state kinetics of the system just described has been studied theoretically by Hanns Fischer, 9 and the predictions of the theory were later tested by experiment. 28 The present study, on the other hand, addresses the question of transient kinetics.…”
Section: Introductionmentioning
confidence: 97%
“…Perhaps the best known types of such radicals are the nitroxide type radicals 20 ͑see the radical P in Scheme I͒ which appear in living free radical polymerization, [21][22][23][24][25] spin trapping reactions, 20 polymer stabilization ͑e.g., by hindered amine light stabilizers-HALS 26,27 ͒, radical scavenging reactions, etc. Some other radical types displaying similarly low self-reactivity are quinone type radicals which arise in the inhibition of free radical chain reactions by phenolic compounds, 28 some cobalt compounds, 29,30 and nitric oxide radicals 31 which have important biological roles.…”
Section: Introductionmentioning
confidence: 99%
“…Fischer et al [24][25][26][27][28][29] developed kinetic models that showed the change of radicals (both nitroxide and propagating) with time. These kinetic models (known as Persistent Radical Effect) proved that the concentration of radicals is not constant with time.…”
Section: Nitroxide Mediated Polymerization (Nmp)mentioning
confidence: 99%
“…For example, α-tocopherol is the major lipidsoluble, chain-breaking antioxidant in human blood plasma and low-density lipoprotein. Phenolic antioxidants mechanism is believed to transfer its phenolic H-atom to chain-carrying radicals and then break the chain process of autoxidants [4][5][6][7][8][9][10][11][12][13][14] . The main reactions can be represented by the following reactions (1) and (2) [13][14][15][16] : ROO·+ ArOH → ROOH + ArO· (1) R· + ArOH → RH + ArO·…”
mentioning
confidence: 99%